Ferrocene-Bis(thymine/uracil) conjugates: base pairing directed, spacer dependent self-assembly and supramolecular packing - Patwa, Amit N.; Gonnade, Rajesh G.; Kumar, Vaijayanti A.; Bhadbhade, Mohan M.; Ganesh, Krishna N. (Journal of Organic Chemistry, 2010)
X-ray crystallographic studies of methylene linked Ferrocene-bis(thymine/uracil) conjugates Fc(T:T)m and Fc(U:U)(M) reveal base dependent 2-D supramolecular assemblies generated via wobble self-pairing for bis-thymine and reverse wobble self-pairing for bis-uracil conjugates, differing in architecture from the corresponding butylene spacer linked conjugates